Chronic developmental hypoxia alters mitochondrial oxidative capacity and reactive oxygen species production in the fetal rat heart in a sex‐dependent manner. Issue 3 (17th August 2022) - Smith, Kerri L. M.; Swiderska, Agnieszka; Lock, Mitchell C.; Graham, Lucia; Iswari, Wulan; Choudhary, Tashi; Thomas, Donna; Kowash, Hager M.; Desforges, Michelle; Cottrell, Elizabeth C.; Trafford, Andrew W.; Giussani, Dino A.; et al.
Abstract: Insufficient oxygen supply (hypoxia) during fetal development leads to cardiac remodeling and a predisposition to cardiovascular disease in later life. Previous work has shown hypoxia causes oxidative stress in the fetal heart and alters the activity and expression of mitochondrial proteins in a sex‐dependent manner. However, the functional effects of these modifications on mitochondrial respiration remain unknown. Furthermore, while maternal antioxidant treatments are emerging as a promising new strategy to protect the hypoxic fetus, whether these treatments convey similar protection to cardiac mitochondria in the male or female fetus has not been investigated. Therefore, using an established rat model, we measured the sex‐dependent effects of gestational hypoxia and maternal melatonin treatment on fetal cardiac mitochondrial respiration, reactive oxygen species (ROS) production, and lipid peroxidation. Pregnant Wistar rats were subjected to normoxia or hypoxia (13% oxygen) during gestational days (GDs) 6–20 (term 22 days) with or without melatonin treatment (5 µg/ml in maternal drinking water). On GD 20, mitochondrial aerobic respiration and H2 O2 production were measured in fetal heart tissue, together with lipid peroxidation and citrate synthase (CS) activity. Gestational hypoxia reduced maternal body weight gain ( p < .01) and increased placental weight ( p < .05) but had no effect on fetal weight or litter size. Cardiac mitochondria from male but not female fetuses of hypoxic pregnancy had reduced respiratory capacity at Complex II (CII) ( p < .05), and an increase in H2 O2 production/O2 consumption ( p < .05) without any changes in lipid peroxidation. CS activity was also unchanged in both sexes. Despite maternal melatonin treatment increasing maternal and fetal plasma melatonin concentration ( p < .001), melatonin treatment had no effect on any of the mitochondrial parameters investigated. To conclude, we show that gestational hypoxia leads to ROS generation from the mitochondrial electron transport chain and affects fetal cardiac mitochondrial respiration in a sex‐dependent manner. We also show that maternal melatonin treatment had no effect on these relationships, which has implications for the development of future therapies for hypoxic pregnancies.